Methodologie Basis for the Radioimmunoassay of Endogenous LH-Like Activity in Human Prostatic Tissue - Dorobek, W.; Misiorowski, W.; Niewiadomska, A.; Baranowska, B.; Kuzaka, B.; Krzeski, T.; Zgliczyński, S. (Nuklearmedizin - NuclearMedicine, 1983)
The aim of this study was to develop a technique for the radioimmunoiogical determination of the activity of LH-like substances in the human prostate. The material comprised 19 specimens of prostatic tissue obtained during transbladder extirpation in patients with benign prostatic hyperplasia. Tissues of human testes and human sceletal muscle were used as controls. The method adopted for LH extraction from the membrane fraction of human prostatic tissue appeared to be sufficiently specific, accurate and sensitive for routine laboratory investigations. The concentrations of the LH-like immunoreactivity in human testicular tissue was found to be 57, 46 and 70 mU per g of the membrane fraction while those of the prostatic gland tissues ranged from 34 to 155 mU per g of the membrane fraction. However such LH-like substance was not found in human sceletal muscle tissue. It seems that the LH-type activity is an indirect proof for the existence of LH receptors in the human prostate.